Sophisticated Linguistic Modal Theories - Marambio, José Tomás Alvarado (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This work presents and discusses three recent proposals for the explanation of possible worlds by means of linguistic constructions. In the first part the main difficulties and objections leveled against the linguistic conception of possible worlds are briefly exposed. Then, the proposals of Roy,Melia and Sider are discussed with some detail. In all three cases a basic problem is pointed out: the proposals work by the introduction of certain linguistic elements (extra names, pixels and quantifiers ranging over possibilia) whose semantic function is never well understood. Those linguistic elements might be intelligible if there were an independent and objective realm of modal facts, but the elements are proposed precisely to play the role of those facts.